Does postexercise static stretching alleviate delayed muscle soreness? - Burkoer, K. C.; Schware, J. A. (The Physician and Sportsmedicine, 1989)
The use of static stretching as part of postexercise recovery to alleviate muscle soreness was found to be ineffective and no different to a group who did no stretching at all. Implication: Stretching as a recovery activity does not reduce muscle soreness.